Salvia hasankeyfense (Lamiaceae), a new species from Hasankeyf (Batman, South-eastern Turkey) - Celep, Ferhat; Dirmenci, Tuncay; Güner, Özal (Phytotaxa, 2015)
The new species Salvia hasankeyfense (Lamiaceae) is here described and illustrated. It is confined to Hasankeyf ancient city, Batman, in South-eastern Turkey where it grows in rocky cracks. It is distinguished from the morphologically similar Salvia verbenaca by chiefly basal and stem leaf shape, size and indumentum, stem indumentum, and corolla colour. IUCN red list category, distribution map, notes on biogeography and ecology of the new species are also given.